PREVALENSI KOKSIDIOSIS PADA PEDET DI KABUPATEN WONOGIRI - , ANDHA ARDIANTO; , Dr. drh. Widagdo Sri Nugroho, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Coccidiosis is a disease caused by Eimeria sp. Coccidiosis in calves inhibited weight gain and reduced its growth. This research were conducted to find out the prevalence of coccidiosis in calves in wonogiri, and indentify risk factors of coccidiosis. Two hundred and fifty nine feces of cattle were taken from 221 farms in Wonogiri. Sampling technics were applied in the research were multistage random sampling, simple random sampling and cluster sampling at farm level. Risk factors were obtained by interviews to the farmers. Laboratory diagnosis was done by floatation method. Data were analized by description statistic, and the association between coccidiosis and risk factors were done by bivariate analysis base on chi square ( Ï2) and odss ratio (OR). The result showed, the prevalence of coccidiosis in calves in Wonogiri was 43,21% (112/259). The risk factors which associated with coccidiosis infection in Wonogiri were the animalâs origin, type of feed, feeding time, and type of enclosure. Farmers should improve the farm management include sanitation of enclosure, feed, and animal health program, to reduce the coccidiosis.